2004
DOI: 10.1002/chin.200443025
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Bismuth Chalcogenide Thin Films Using Novel Single‐Source Precursors by Metal‐Organic Chemical Vapor Deposition.

Abstract: cursors by Metal-Organic Chemical Vapor Deposition. -The metal-organic compounds Bi[(EPR2)2N]3 (E: S, Se; R: Ph, iPr), are used as single-source precursors for the deposition of bismuth chalcogenide thin films via low-pressure and aerosol-assisted metal-organic chemical vapor deposition. Crystalline thin films of rhombohedral Bi 2 Se 3 (using Bi[(SeP(iPr) 2 ) 2 N] 3 ), hexagonal BiSe (from Bi[(SePPh 2 ) 2 N] 3 ), and orthorhombic Bi2S3 (from Bi[(SPR2)2N]3) are deposited on glass substrates. The produced films … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 1 publication
2
21
0
Order By: Relevance
“…It can therefore be concluded that nuclei yielding platelets represent the lowest surface energy. The same microplatelets were observed by others [4] using single source MOCVD at precursor temperature of 275…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…It can therefore be concluded that nuclei yielding platelets represent the lowest surface energy. The same microplatelets were observed by others [4] using single source MOCVD at precursor temperature of 275…”
Section: Resultssupporting
confidence: 82%
“…Recently, research attention geared toward chemical and electrochemical synthesis of nanostructured colloidal chalcogenide semiconductors has increased several folds [1][2][3][4][5][6][7][8][9][10]. In this group, Bi 2 Se 3 nano-and microsised clusters, isolated or well-adhered morphological orientations have been reported in literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many metal chalcogenide materials can be deposited via CVD techniques and this has stimulated a large amount of work on the development of tailored CVD precursors for their production1314151617. CVD has mostly been used to achieve planar films rather than selective hole filling, and area selective growth is not a natural feature of CVD.…”
mentioning
confidence: 99%
“…Recently, the increasing interest in synthesis of thin films from various semiconductive materials for their application in many areas of technology has been observed: in solar cells, sensors, optical storage devices ets. [1][2][3][4][5][6][7].…”
mentioning
confidence: 99%